1980
DOI: 10.1111/j.1471-4159.1980.tb03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal Site of Action for Imipramine in Rat Striatal Slices

Abstract: The uptake of 3H-labeled imipramine ([3H]IMI) in rat carpus striatum slices was found to be strongly temperature-dependent. The accumulation was shown to be saturable and two apparent Km's were found: 2.2 x 10(-8) and 3.5 x 10(-7) M. Once incorporated, the labeled drug was released from superfused slices by K+ (55 mM) depolarization in the presence of calcium ions. Imipramine was also studied for its ability to induce the release of [3H]dopamine ([2H]DA) which had been previously accumulated by striatal slices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
2
4
1
Order By: Relevance
“…The absence of an active transport system further militates against an intraneuronal (vesicular) site of action of imipramine (Daniels et al, 1980). In the present study, although the accumulation of ['Hlimipramine into slices was temperature sensitive, it was not saturable, and no concentration of radiolabel relative to the incubation medium was achieved.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The absence of an active transport system further militates against an intraneuronal (vesicular) site of action of imipramine (Daniels et al, 1980). In the present study, although the accumulation of ['Hlimipramine into slices was temperature sensitive, it was not saturable, and no concentration of radiolabel relative to the incubation medium was achieved.…”
Section: Discussioncontrasting
confidence: 47%
“…Paradoxically, however, subcel-M a r distribution studies have indicated that [3H]imipramine may be associated with synaptic vesicles (Okada et al, 1979) rather than with nerve terminal membranes (Laduron et al, 1982). Consistent with an intraneuronal site of action is the report that [3H]imipramine is accumulated by rat striatal slices (Daniels et al, 1980). The above-mentioned studies were carried out either at relatively high imipramine concentrations in tissue slices under "physiological" conditions or at lower imipramine concentrations in membrane preparations under nonphysiological conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been shown that [3H]desipramine can be accumulated in nerve endings (Yavin et al, 1979) and it was suggested that ["Hlimipramine can be stored in vesicles located in central catecholaminergic nerve endings (Daniels et al, 1980). On the basis of the fact that potassium could release radioactivity from rat striatal slices preincubated with ["Hlimipramine, these authors postulated that imipramine itself can be released like a neurotransmitter and that the antidepressant effects of imipramine may be partly related to its role as a false neurotransmitter (Daniels et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that [3H]imipramine is accumulated by rat striatal slices and that it can be released by potassium depolarization, suggesting vesicular storage and a false transmitter role for the antidepressant drug (Daniels et a]., 1980). The aim of the present experiments was to investigate further this possibility by studying the uptake and release of ["Hlimipramine in two areas of the rabbit brain: the caudate nucleus and the hypo-thalamus.…”
mentioning
confidence: 89%